Kedaulatan Siber: Tantangan dan Implikasi terhadap Hukum Internasional Modern - Indra Duari; Muhammad Saiful; Heri Pratama (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The rapid development of information and communication technology has created a new dimension in the global order—cyberspace, which has become a strategic arena in international relations. This phenomenon raises fundamental questions regarding the concept of state sovereignty in cyberspace and how international law governs it. This study aims to analyze the principles of sovereignty within the cyber context and their implications for modern international legal frameworks. The research employs a normative approach by examining various international legal instruments such as the UN Charter, the Tallinn Manual 2.0, and conventions related to cybersecurity. The findings reveal that cyber sovereignty is not explicitly regulated in existing international legal instruments; however, the fundamental principles of state sovereignty remain applicable in this domain. Actions such as cyberattacks between states may be categorized as violations of sovereignty or even acts of aggression if they threaten a nation’s security. Moreover, there is an ongoing tension between national security interests and the principle of freedom of expression as recognized in international law. This study concludes that there is an urgent need for the establishment of more specific international legal norms to govern cyber activities, in order to prevent inter-state conflicts and ensure that the fundamental principles of international law are upheld in the digital era. The creation of a global legal framework for fair, inclusive, and transparent cyber governance is essential to promote stability and justice in modern international relations.